Universal limiting shape of worn profile under multiple-mode fretting conditions: theory and experimental evidence; Scientific Reports; Vol. 6 - Dmitriev A. I. Andrey Ivanovich; lars B. V.; Psakhie S. G. Sergey Grigorievich; Popov V. L. Valentin Leonidovich (2015, 2015)
Title screen